2023
DOI: 10.2196/42864
|View full text |Cite
|
Sign up to set email alerts
|

Providing Human Support for the Use of Digital Mental Health Interventions: Systematic Meta-review

Abstract: Background Digital mental health interventions (DMHIs) have been increasingly deployed to bridge gaps in mental health care, particularly given their promising efficacy. Nevertheless, attrition among DMHI users remains high. In response, human support has been studied as a means of improving retention to and outcomes of DMHIs. Although a growing number of studies and meta-analyses have investigated the effects of human support for DMHIs on mental health outcomes, systematic empirical evidence of it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 82 publications
1
16
0
3
Order By: Relevance
“…Digitale Interventionen, insbesondere Apps, können entweder „geleitet“ sein (Unterstützung und Feedback durch Therapeut:in in Form von Textnachrichten oder Telefonanrufen) oder sie werden „ungeleitet“ durchgeführt. Die momentane Forschungslage legt nahe, dass geleitete digitale Interventionen effektiver sind als ungeleitete [ 22 ]. Grundsätzlich ist die Abbruchquote bei digitalen Interventionen hoch.…”
Section: Anwendungsgebiete Und Evidenz Von Digitalen Technologien Im ...unclassified
See 2 more Smart Citations
“…Digitale Interventionen, insbesondere Apps, können entweder „geleitet“ sein (Unterstützung und Feedback durch Therapeut:in in Form von Textnachrichten oder Telefonanrufen) oder sie werden „ungeleitet“ durchgeführt. Die momentane Forschungslage legt nahe, dass geleitete digitale Interventionen effektiver sind als ungeleitete [ 22 ]. Grundsätzlich ist die Abbruchquote bei digitalen Interventionen hoch.…”
Section: Anwendungsgebiete Und Evidenz Von Digitalen Technologien Im ...unclassified
“…Strategien, um Patient:innen in einer digitalen Intervention für die psychische Gesundheit zu halten, wurden auch von Wissenschaftler:innen des Leibniz WissenschaftsCampus Digital Public Health (LWC DiPH) untersucht. Diese reichen von Feedback in Bezug auf das eigene Wohlergehen über die Beantwortung von Fragen zu Inhalten der Intervention bis hin zur Einbindung der Teilnehmer:innen in soziale Foren [ 22 , 24 ].…”
Section: Anwendungsgebiete Und Evidenz Von Digitalen Technologien Im ...unclassified
See 1 more Smart Citation
“…[33] However, some meta-analyses have raised questions about whether self-guided apps are effective in improving mental health [34,35]. Other reviews have concluded that interventions incorporating human support (e.g., coaching, manual adherence prompts, or integration with professional face-to-face care) yield greater effectiveness [36,37] and adherence [38,39] than self-guided apps. If smartphone apps need human support to be effective, this resource limitation must be factored into implementation of digital interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the efficacy, effectiveness, and implementation of clinician-supported digital applications designed for individuals with mental illness supports the use of a digital interventionist in the administration of mHealth and its integration into treatment plans and delivery (Ben-Zeev et al, 2015 ; Mohr et al, 2021 ; Schueller et al, 2016 ; Wisniewski & Torous, 2020 ; Wisniewski et al, 2020 ). A recent meta-systematic review, which analyzed the results of 31 meta-analyses consisting of 505 independent trials (Werntz et al, 2023 ), found larger effect sizes among digital mental health intervention trials that included human-supported mHealth interventions. Moreover, the meta-systematic review concluded that human-supported mHealth interventions may be more effective than unsupported interventions for individuals with greater symptom severity.…”
mentioning
confidence: 99%